Fruit weight of coffee beans from an pollinator/vertebrate-exclosure experiment conducted in three different land use types at Mount Kilimanjaro - Alice Classen; Stefan W Ferger; Maria Helbig-Bonitz; Marcell Karl Peters; Julia Schmack; Matthias Schleuning; Katrin Böhning-Gaese; Ingolf Steffan-Dewenter (PANGAEA, 2018)
Wild animals substantially support crop production by providing ecosystem services, such as pollination and natural pest control. However, the strengths of synergies between ecosystem services and their dependencies on land-use management are largely unknown. Here, we took an experimental approach to test the impact of land-use intensification on both individual and combined pollination and pest control services in coffee production systems at Mount Kilimanjaro. We established a full-factorial pollinator and vertebrate exclosure experiment along a land-use gradient from traditional homegardens (agroforestry systems), shaded coffee plantations to sun coffee plantations (total sample size = 180 coffee bushes). The exclusion of vertebrates led to a reduction in fruit set of ca 9%. Pollinators did not affect fruit set, but significantly increased fruit weight of coffee by an average of 7.4%. We found no significant decline of these ecosystem services along the land-use gradient. Pest control and pollination service were thus complementary, contributing to coffee production by affecting the quantity and quality of a major tropical cash crop across different coffee production systems at Mount Kilimanjaro.
Supplement to: Classen, Alice; Peters, Marcell Karl; Ferger, Stefan W; Helbig-Bonitz, Maria; Schmack, Julia; Maassen, G; Schleuning, Matthias; Kalko, Elisabeth K V; Böhning-Gaese, Katrin; Steffan-Dewenter, Ingolf (2014): Complementary ecosystem services provided by pest predators and pollinators increase quantity and quality of coffee yields. Proceedings of the Royal Society B-Biological Sciences, 281(1779), 20133148-20133148, https://doi.org/10.1098/rspb.2013.3148